LEMAHNYA KECERDASAN SPIRITUAL DALAM KEPEMIMPINAN BANGSA INDONESIA (Sebuah Tinjauan Character Building Bangsa Menurut Perspektif Hindu) - AA Raka Mas (Jurnal PASUPATI, 2013)
AbstractThis article should try to describe the leadership of our nation to day, using the break of spiritual as the strategie issue. The fenomena that exist in our country were “the raising”, of corruption, murder, robbery, and the other amoral behavior or moral degradition. These all of condition motivating me to know the problem and searching the volution. The metodology applying in this article was descriptif an kwalitatif method. Hoping this article will be have any value.Keywords : leadership, spiritual intellegences, nation, character building